Augmented Reality Menggunakan Marker Based Tracking Untuk Informasi Sejarah Kain Tapis Lampung - Setiawan, Asep Trisna; Dika Hastanto; Dian Resha Agustina; Adi Permana; Dewi Tresnawati, Dewi Tresnawati (Institut Teknologi Garut, 2025)
Lampung Tapis fabric is one of Indonesia's cultural heritages that possesses its own unique charm and beauty. This fabric originates from Lampung, a province on the island of Sumatra, Indonesia. Lampung Tapis fabric features distinctive patterns, motifs, and production techniques, and is believed to hold significant historical and symbolic value for the Lampung community. In the era of rapidly advancing digital technology, Augmented Reality (AR) has emerged as an innovative tool for preserving, promoting, and safeguarding cultural heritage. AR is a technology that blends the real world with virtual or additional elements through the use of electronic devices such as smartphones or tablets, enabling users to interactively experience digital content within a real-world physical context. One of the main issues is the lack of a complete history of the Lampung Tapis Fabric exhibited at the Ruwa Jurai Museum in Lampung, which poses a challenge as it results in insufficient historical information to understand the origins, development, and value contained within this cultural heritage. As a result, there is a risk of losing valuable information about local cultural heritage. This research has successfully developed an Augmented Reality application that provides information about the Lampung Tapis Cloth, thereby reducing the potential loss of cultural heritage information in Lampung.